“Quiet Americans in India”: the CIA and the politics of intelligence in Cold War South Asia - McGarr, Paul M. (Oxford University Press, 2014)
In February 1967, officials from the Central Intelligence Agency (CIA) were horrified when the American west-coast magazine, Ramparts, exposed the U.S. intelligence organization’s longstanding financial relationships with a number of international educational institutions and cultural bodies. In a series of articles, reproduced in The New York Times and The Washington Post, Ramparts documented the CIA’s provision of covert funding to, among others, the National Students Association, Asia Foundation, and Congress for Cultural Freedom (CCF). In India, an outpouring of public indignation ensued when it became clear that the Indian Committee for Cultural Freedom, a local offshoot of the CCF, had accepted money from the CIA. The global spotlight cast upon some of the CIA’s more questionable activities had a profound and enduring impact upon Indian perceptions of the United States’ government and its external intelligence service. In the wake of the Ramparts scandal, the CIA came to occupy a prominent place in Indo–U.S. cultural and political discourse. For the remainder of the twentieth century, and beyond, anti-American elements inside and outside India drew repeatedly upon the specter of CIA subversion as a means of undermining New Delhi’s relationship with Washington.